Optimasi Proses Produksi UMKM Percetakan Canaprint Berdasarkan Waktu dan Biaya Menggunakan Metode Multi-Objective Optimization - Saskia Syafa Azahra; Naella Laurensia Simanjuntak; Esa Faiz Nurdin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
Canaprint printing MSME is a business engaged in printing services with the main problems of high production costs and long order completion time. These problems are caused by inefficient use of materials and unstructured production scheduling. This study aims to optimize the production process of Canaprint MSME based on two main criteria, namely production time and production cost using the Multi-Objective Optimization (MOO) method. The method used in this study is the Weighted Sum method by combining two objective functions into a single optimization function. The research data were obtained through direct observation, interviews, and production data recording. The results show that the application of the Multi Objective Optimization method is able to provide a more optimal production sequence alternative, so that it can reduce production costs and accelerate order completion time. Therefore, this method can be used as a basis for decision making in production scheduling at Canaprint printing MSME.